RGS14 binds to GNAI3 and regulates the proliferation and apoptosis of human spermatogonial stem cells by affecting PLPP2 expression and MAPK signaling - Liu, Bang; Deng, Aimin; Liu, Lvjun; peng, Lin; Liu, Xiaowen; Chen, Xiangyu; Zhu, Fang; Zhang, Shusheng; Zhou, Dai (Frontiers in Cell and Developmental Biology, 2025)
BackgroundNon-obstructive azoospermia (NOA) represents a severe form of male infertility, characterized by the absence of sperm in the ejaculate due to impaired spermatogenesis. Spermatogonial stem cells (SSCs), which ensure continuous sperm production, are critical for maintaining male fertility. Despite their importance, the molecular mechanisms governing SSC fate determination and their role in NOA pathogenesis remain incompletely understood. This study investigates the regulatory networks underlying SSC dysfunction in NOA patients.ResultsUsing single-cell RNA sequencing, we identified significant downregulation of RGS14 in SSCs of NOA patients compared to normal testes. Immunofluorescence validation confirmed RGS14 localization primarily in SSCs. Functional assays demonstrated that RGS14 knockdown in SSC lines markedly suppressed cell proliferation and induced apoptosis. RNA-sequencing analyses revealed that RGS14 deficiency inhibited PLPP2 expression and MAPK signaling activation. Notably, PLPP2 overexpression rescued the phenotypic defects caused by RGS14 depletion. Protein-protein interaction assays and co-immunoprecipitation experiments further established that RGS14 physically interacts with GNAI3 to coordinately regulate cell proliferation and PLPP2 expression. Expression validation in NOA testes demonstrated concurrent downregulation of GNAI3 and PLPP2 in NOA patients, implicating their dysregulation in spermatogenic failure.ConclusionOur findings uncover a novel RGS14-GNAI3-PLPP2 regulatory axis critical for SSC homeostasis. The dysregulation of these molecules contributes to SSC dysfunction and NOA pathogenesis. These data not only elucidate RGS14's role in SSC fate determination but also identify RGS14 and its interactome as promising therapeutic targets for restoring spermatogenesis in male infertility.